FISHERMAN’S WIFE PERCEPTION TO MANAGE TIME FOR PROVIDING INCOMES ACTIVITY AT MELAI VILLAGE WEST RANGSANG DISTRICT KEPULAUAN MERANTI RIAU PROVINCE - Rohani '; Kusai '; Zulkarnaini ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
ABSTRACTThis research was conducted in July 2014 on Melai village West Rangsang District Kepulauan Meranti Riau Province. The location was deliberately determined ( purposive ). The method used in this study is survey method, the type of data, obtained directly from the first responden, the secondary data of additional data such as geographic location, demographic total population, total population besed on gender. The purpose of this research was to determine the fisherman’s wife perception to manage time for providing incomes activity.The fisherman’s wife characteristic in Melai Village consist of 7 persons (43.75% ) at 32 – 37 years old, thas have graduated primary school. Fisherman’s wife in Melai Village dominated as a farmer about 10 persons (62.50 %) . Fisherman’s wife perception to manage tie for providng income activity that lacated in agree rate was 6 person with the score about 1306- 1680. While spending time for activities that not able to generate revenue at agree category and spending daily time at disagree category.